Community networks: identifying social capital in Emerado, North Dakota - Atkinson, Lisa (Kansas State University, 2014)
The City of Emerado, North Dakota, population 414, located in northeast North Dakota is the subject of a Social Network Analysis (SNA), conducted prior to it being the subject of a University of North Dakota Center for Community Engagement, Community Connect Forum. The SNA was developed based on the results of 25 interviews conducted with local residents, elected officials and business owners, using snowball sampling and following grounded theory methods. The interview results were coded and memos were written to aid in the analysis. Social Network data was entered into the Sentinel Visualizer software (FMS Advanced Systems Group) to develop a visual image of the network, including nodes (people, organizations or businesses) and links to illustrate the relationships between nodes. The SNA helps to frame the relationships in terms of bridging and bonding social capital. The SNA provides the ability to mathematically determine the most important nodes to the community social network, using calculations to determine levels of degree centrality, betweenness centrality, closeness centrality, Eigenvalue, and network density. After calculating these elements, categorical descriptions of the top ten individuals for each category are provided. The networks of five individuals are reviewed in depth to aid in comprehending the process of incrementally expanding networks.
Keywords: Community development; Social network analysis; Social network mapping; Grounded theory; Snowball sample; Social capital; Area Planning and Development (0341); Regional Studies (0604); Social Research (0344)